Translabyrinthine Approach for Resection of Vestibular Schwannoma - Feng, Yening; Patel, Neil S.; Gompel, Jamie J. Van; Carlson, Matthew L. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives This video describes the surgical indications, relevant anatomy, and surgical steps of routine translabyrinthine surgery for gross total resection of sporadic vestibular schwannoma.Design The procedure is presented through a surgical instructional video.Setting The surgery took place at tertiary skull base referral center.Parcipant A 47-year-old patient reported with nonserviceable hearing, frequent episodes of vertigo, recurrent severe headache, and a small unilateral right sided vestibular schwannoma.Results Gross total resection with preservation of facial nerve function was achieved.Conclusion This instructional video documents the surgical steps and relevant anatomy for translabyrinthine resection of vestibular schwannoma.The link to the video can be found at: https://youtu.be/CJ2vKMLs7aI.
Keywords: translabyrinthine; vestibular schwannoma; acoustic neuroma